Don Juan - Byron, George Gordon Byron, Baron, 1788-1824 (Floating Press, 2009)
In his satiric poem Don Juan , Lord Byron refigures the legend as a man easily seduced by women, rather than as a dangerous womanizer. When the first two cantos were anonymously published in 1819, they were criticized for being immoral. They were also immensely popular. Byron only completed 16 cantos, leaving the 17th unwritten when he died in 1824. Don Juan is commonly considered to be his masterpiece.